2021
DOI: 10.1371/journal.pgen.1009986
|View full text |Cite
|
Sign up to set email alerts
|

Co-existing TP53 and ARID1A mutations promote aggressive endometrial tumorigenesis

Abstract: TP53 and ARID1A are frequently mutated across cancer but rarely in the same primary tumor. Endometrial cancer has the highest TP53-ARID1A mutual exclusivity rate. However, the functional relationship between TP53 and ARID1A mutations in the endometrium has not been elucidated. We used genetically engineered mice and in vivo genomic approaches to discern both unique and overlapping roles of TP53 and ARID1A in the endometrium. TP53 loss with oncogenic PIK3CAH1047R in the endometrial epithelium results in feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 145 publications
(200 reference statements)
2
24
0
Order By: Relevance
“…There were no obvious sarcomatous elements in any of the tumors. High-grade nuclear atypia (consistent with severe aneuploidy) was not observed, as in most prior mouse models ( 48 51 ). Thus, histologically, the Foxa2 / Pten tumors resembled well-differentiated (i.e., grade 1) human endometrioid adenocarcinomas ( Figure 4, F and G ).…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…There were no obvious sarcomatous elements in any of the tumors. High-grade nuclear atypia (consistent with severe aneuploidy) was not observed, as in most prior mouse models ( 48 51 ). Thus, histologically, the Foxa2 / Pten tumors resembled well-differentiated (i.e., grade 1) human endometrioid adenocarcinomas ( Figure 4, F and G ).…”
Section: Resultsmentioning
confidence: 49%
“…We then explored the possibility that Tp53 mutations occur in the tumors by p53 IHC (a sensitive and specific surrogate of mutations) at necropsy in n = 23 mice from the survival analysis. None of the tumors exhibited p53 mutant (overexpressing) clones, which provides an argument that, unlike some other mouse models and human cancer types, p53 mutation is not essential for Foxa2 -driven tumors ( 43 , 44 , 48 , 51 , 52 ). Taken together, these results demonstrated that Foxa2 was a potent tumor suppressor where functional inactivation cooperated with Pten loss.…”
Section: Resultsmentioning
confidence: 76%
“…The pharmacological study suggested that G. baccata extract can upregulate AKT1 gene expressions to protect the cells against oxidative damage and inflammation ( Martínez et al, 2021 ). Moreover, the studies also suggested that TP53, PIK3R1, and PIK3CA were vital for inflammation ( Eyileten et al, 2018 ; Busbee et al, 2021 ; Reske et al, 2021 ). Accordingly, the results indicate that emodin, aloe-emodin, rhein, luteolin, and quercetin may play an important role in inhibiting anti-inflammatory and anti-oxidative damage.…”
Section: Resultsmentioning
confidence: 99%
“…A more plausible mechanism for the triggering of extraordinary inflammation in Ltf iCre/+ Arid1a f/f pregnant uteri is suggested by the fact that epithelial cells in the uterus as well as in other tissue types are known to produce TNF, CSF2, and other proinflammatory cytokines in certain circumstances [ 42 , 58 , 59 , 60 , 61 ]. In fact, ARID1A has been shown to directly bind near the promoter regions of Il36a , Tnfsf13 , and other TNF-signaling related genes in the murine endometrial epithelium [ 30 ]. Furthermore, in 12Z endometriotic epithelial cells, genes bound by ARID1A and upregulated by knockdown of ARID1A expression include TNF signaling-related and inflammatory response pathway genes [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies using mouse models have shown that deletion of uterine Arid1a drives increased endometriosis-like lesion establishment and causes endometrial-factor infertility related to disrupted P4 and E2 signaling [ 22 , 24 , 28 ]. Focused study on the role of ARID1A in the endometrial epithelium has revealed its critical cell-type-specific roles of maintaining epithelial identity and enabling gland development and function in pregnancy [ 29 , 30 , 31 ]. Deletion of Arid1a in the adult mouse endometrial epithelium led to early pregnancy defects through attenuation of forkhead box A2 (FOXA2) expression and LIF secretion from uterine glands.…”
Section: Introductionmentioning
confidence: 99%